Weaponry and Equipment of the Irish Republican Army during the Irish War of Independence (1919–1921) - Pawłowska, Antonina (Vade Nobiscum, tom XX/2019: Studia z historii politycznej i wojskowej, 2019)
The article presents an analysis of the logistics and the supply base of the Irish side of the conflict during the Tan War. The issues examined are: the state of the finances of both sides of the conflict and the methods of raising funds needed to wage war; the matter of firearms and acquiring them; production and use of the explosives. Means of transport used by both sides are also considered. as well as medical assistance, uniforms and provisioning. The article is based on witnesses’ testimonies gathered. by the Bureau of the Military History.